2015
DOI: 10.1016/j.proeng.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trabecular Bones Microarchitectures and Crystal Structure of Hydroxyapatite in Bone Osteoporosis with Application of the Rietveld Method

Abstract: The term crystal structure is understood as a set of atoms periodically distributed in space, forming a lattice. The composit e material, bone, contains an organic part consisted of collagen and an inorganic part consisted predominantly of hydroxyapatite crystals, having the molecular formula Ca10(PO4)6(OH)2 in its unit cell. The crystal structure of hydroxyapatite can indicate the trabecular bone quality, by the identification of crystallite size, microhardness, microstrain and ratio of calcium and phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Some studies [31,71] showed that increasing the calcination temperature results in an increase in the size of the crystallite; however, the results showed that for the same calcination temperature (800 °C), the crystallite size was larger for the sample 1, obtained from the precursor of biological origin. The sizes of crystallites were calculated indicating that the larger crystallite sizes are associated with normal bone [72]. In the samples synthesized in this work we verified this larger size in sample 1, synthesized from the biological precursor.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Some studies [31,71] showed that increasing the calcination temperature results in an increase in the size of the crystallite; however, the results showed that for the same calcination temperature (800 °C), the crystallite size was larger for the sample 1, obtained from the precursor of biological origin. The sizes of crystallites were calculated indicating that the larger crystallite sizes are associated with normal bone [72]. In the samples synthesized in this work we verified this larger size in sample 1, synthesized from the biological precursor.…”
Section: Resultssupporting
confidence: 64%
“…In the samples synthesized in this work we verified this larger size in sample 1, synthesized from the biological precursor. Rollo et al [72] showed that the crystal structure of hydroxyapatite may indicate the quality of the trabecular bones, by identifying the size of the crystallite, microhardness, microstrain and calcium and phosphorus ratio in bones of three types: normal, osteopenic or osteoporotic. That means that Rietveld analysis should be a practical tool to evaluate the health of individuals through the diffraction study of their skeletal remains.…”
Section: Resultsmentioning
confidence: 99%
“…This is entirely consistent with the observations of this study and indicates possible specific differences in apatite chemistry between the fracture and non-fracture groups. Disorder within the apatite lattice, as introduced by such lattice site modifications, has been proposed as a fundamental contributor to bone mechanical compromise for more than three decades 23 and evidence for this hypothesis continues to be reported 24 . Consequently, the chemical composition of bone apatite through its influence on crystallite dimensions and subsequently micro-architecture is a significant determinant of bone mechanical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Along with calcium, inorganic (i) phosphate (Pi) is the main constituent of hydroxyapatite, the bone mineral that strengthens the mechanical resistance of the organic matrix. Of note, in human adult body, about 90% of total phosphorus is stored in the bone as hydroxyapatite (calcium-phosphate) crystals whose structure is indicative of trabecular bone quality [5,6]. Regulation of phosphate balance relies on a fine-tuning Prof. Maria Luisa Bianchi passed away prior manuscript submission.…”
Section: Introductionmentioning
confidence: 99%